(untitled) (Ameghiniana, 2013)
Simpsonotus praecursor gen. et sp. nov. and Simpsonotus major sp. nov. (Notoungulata, Henricosborniidae) represent the first fossil mamrnals found in the lower part (Mealla Formation) of the Santa Bárbara Subgroup (Salta Group). The occurrence of these particular fossils confirm a Tertiary age for the entire Santa, Bárbara Subgroup. Based on these taxa the Mealla Formation is correlated, at least in part, with the Riochican Land-mammal age (conventionally Late Paleocene) of Patagonia. Simpsonotus remains are the most complete Henricosborniidae thus far known and, based on its auditory region, are now recognized as the most primitive South American Notoungulata yet discovered. The primitive auditory structure of Simpsonotus suggests a distant relationship with other South American Notioprogonia (i.e. family Notostylopidae). If the characters in Simpsonotus are shared by other Henricosborniidae, then the family would deserve recognition as a distinct Suborder of the Notoungulata.